Corporate Governance Mechanisms As Antecedent And Financial Distress As Consequence Of Credit Risk In The Iraqi Banks - Mohammed Sadaa, Abdullah (2023)
This study aimed to examine the connection between corporate governance mechanisms (board structure and ownership structure) and credit risk. Besides, examines the effect of credit risk on financial distress. The study examines the moderating effect of ownership concentration between credit risk and financial distress as well.